Knowledge, attitude and practice about health promotion amangst phystiotherapists in South Africa - N.P. Taukobong; H. Myezwa; S. Pengpid; J.P. Van Geertruyden (AOSIS, 2014)
The increasing prevalence of non-communicable chronic diseases, particularly in middle-income countries like South Africa, call for physiotherapists in the 21st century to adopt a health promotion approach in patient treatment.